Forms of Realism Today : Federal Republic of Germany. - Baselitz, Georg; Becker, Wolfgang; Buchrieser, Franz; Escher, Rolf; Grochowiak, Thomas; Grützke, Johannes; Hahn, Friedemann; von Holst, Christian; Hülsmann, Dieter; Janssen, Horst; Klapheck, Konrad; Maether, Christiane; et al. (Vancouver : Vancouver Art Gallery, 1980)
Albert, Hermann ; Baselitz, Georg ; van Dülmen, Gerd ; Escher, Rolf ; Göttlicher, Erhard ; Grützke, Johannes ; Hahn, Friedemann ; Janssen, Horst ; Klapheck, Konrad ; Klasen, Peter ; Maether, Christiane ; Marwan ; Nagel, Peter ; Petrick, Wolfgang ; Reuter, Hans Peter ; Richter, Gerhard ; Sartorius, Malte ; Schmitz, Wolfgang ; Sorge, Peter ; Tripp, Jan Peter ; Ullrich, Dietmar ; Vogelgesang, Klaus ; Vostell, Wolf ; Willikens, Eberhard Günther
biografie
Forms of Realism Today - Federal Republic of Germany, Vancouver Art Gallery, Vancouver, June 7 to July 20, 1980
Text French-English
kunstcatalogus
Keywords: Duitsland